2012
DOI: 10.1590/s0066-782x2012000100020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação hemodinâmica na insuficiência cardíaca: papel do exame físico e dos métodos não invasivos

Abstract: Among the cardiovascular diseases, heart failure (HF) has a high rate of hospitalization, morbidity and mortality, consuming vast resources of the public health system in Brazil and other countries. The correct determination of the filling pressures of the left ventricle by noninvasive or invasive assessment is critical to the proper treatment of patients with decompensated chronic HF, considering that congestion is the main determinant of symptoms and hospitalization. Physical examination has shown to be inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Over the last decade, non-invasive hemodynamic assessment methods including ICG, echocardiography, brain natriuretic peptide (BNP) or lung ultrasound have been increasingly used. 4,5 ICG enables continuous, beat-by-beat, operator-independent cardiac output (CO) monitoring in medical or surgical patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, non-invasive hemodynamic assessment methods including ICG, echocardiography, brain natriuretic peptide (BNP) or lung ultrasound have been increasingly used. 4,5 ICG enables continuous, beat-by-beat, operator-independent cardiac output (CO) monitoring in medical or surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…In HF monitoring, ICG presented hemodynamic results comparable with those obtained by cardiac magnetic resonance 13 and good correlation with invasive methods determinations (notably the Swan-Ganz catheter), with correlation coefficients between 0.76 and 0.89. 4,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While physical examination has many disadvantages, such as low sensitivity, insufficient reliability, and lack of reproducibility, it has the advantages of being noninvasive, time-saving, and economical (3). Physical examination can be performed anytime, anyplace, and many times over.…”
mentioning
confidence: 99%
“…Therefore, it plays an important role in monitoring the changes of pathophysiology in real time. Although a comprehensive and non-selective compilation of physical signs is no longer considered useful (4), selected physical examination can provide definite signs of a disease with good specificity, quantitative evaluation of the disease (3), and thus sometimes make it possible to make a "snap diagnosis" in a short time (5). One study reported that among patients newly admitted to an internal medicine department, 20% could be correctly diagnosed at admission based on the medical history alone and 40% with the combination of history and physical examination (6).…”
mentioning
confidence: 99%